Edukasi Pemanfaatan Lahan Terbatas: Budikdamber dan Hidroponik Sebagai Upaya Pemenuhan Kebutuhan Pangan Keluarga Selama Pandemi Covid-19 - Idola Dian Nebore; Insar Damopolii; Jeni Jeni; Silvia H. K. Sirait; Hengky L. Wambrauw (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
Community service activities were held on July 11, 12 & 30, 2021 at RT 0-02 / RW 09 and RT04/RW02, Amban Village of West Papua. Budikdamber and hydroponics are alternative development techniques for fish and vegetable cultivation on limited land. This activity is limited by the Implementation of PPKM in Manokwari Regency, which began on July 12, 2021. This activity is divided into two, namely, making educational videos offline and sharing educational videos online using the WhatsApp application. There were 22 respondents at RT 0-02 / RW 09 and 7 respondents at RT04/RW02. The average community satisfaction with devotion is 85.55%, with the category "excellent".